MANAGEMENT OF FACIAL PALSY CAUSED BY OTOLOGIC PATHOLOGY - CASE REPORT - Cristian Mârtu; Luminita Rădulescu; Dan Mârtu; Sebastian Cozma (Romanian Society of Oral Rehabilitation, 2014)
Facial palsy is an invalidating condition especially through the associated aesthetic sequelae. Early diagnosis followed by optimal treatment is of crucial importance for functional rehabilitation of the facial nerve. The first step is the establishment of the etiological factor. One first clue regarding the etiology might be represented by the onset mode of the facial palsy but the value of this sign is questionable. There are cited cases in the literature when a benign or malign tumor will be noticed after sudden onset of facial palsy and not as usual after a progressive symptomatology. This study reports a case of peripheral recurrent facial palsy of congenital cholesteatoma etiology. It is described the onset of the palsy, patient evaluation protocol with special emphasis on differential diagnose, stages needed for treatment and post-operative follow-up.